GOALS AND OBJECTIVES OF TEACHERS IN A CLASSROOM (Ustozlar uchun, 2025)
This article explores the goals and objectives of teachers in the classroom. It provides a detailed analysis of teachers’ pedagogical goals, specific and measurable objectives, and strategies to achieve them. The paper also emphasizes the importance of setting goals and objectives for effective teaching and learning outcomes.